2017
DOI: 10.1002/ldr.2840
|View full text |Cite
|
Sign up to set email alerts
|

Spatial patterns of sediment connectivity in terraced lands: Anthropogenic controls of catchment sensitivity

Abstract: In recent decades, the dynamics of global change in developed countries has led to significant alterations in the hydrological and sediment dynamics of terraced land. Agricultural terraces were built to control overland flow and prevent erosion, acting as buffers and barriers throughout the sediment cascading system. Their abandonment and degradation increase the sensitivity of the catchment, promoting the collapse of dry‐stone walls and the reworking of stored sediment. In this study, a geomorphometric index … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 51 publications
1
45
0
1
Order By: Relevance
“…In turn, Calsamiglia et al . (), applying the morphometric Index of Connectivity (IC) in our studied catchment, observed important decoupling effects. Results of this study showed that 62% of the area covered by terraces had lower IC values than the average of the catchment.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In turn, Calsamiglia et al . (), applying the morphometric Index of Connectivity (IC) in our studied catchment, observed important decoupling effects. Results of this study showed that 62% of the area covered by terraces had lower IC values than the average of the catchment.…”
Section: Discussionmentioning
confidence: 86%
“…As a result of past intensive farming, agricultural terraces (i.e. terraced fields, step terraces and check dam terraces) occupy 37% of the area (179 ha) with a total length of 147 km of dry‐stone walls (Figure (c)), of which 75.1 ha are well‐maintained and 103.7 ha abandoned, with an average collapse point density of 12 collapses km −1 and 55 collapses km −1 , respectively (Calsamiglia et al ., ).…”
Section: Study Areamentioning
confidence: 97%
“…IC calculations confirmed that the construction of terraces and their subsequent abandonment induced changes in the spatial patterns of hydrological and sediment connectivity [20], favoring enhanced concentration of surface runoff and, consequently, further development of erosion processes. Previous studies in the Sa Font de la Vila catchment showed that terrace abandonment triggered feedback dynamics in which the collapse of the walls generated increased connectivity, which in turn exacerbated the erosion processes leading to their collapse [11]. The most connected areas within terraces showed clear evidence of erosion along preferential pathways, which may be strongly related to soil and organic matter losses, with negative effects on microbiological communities and enzymatic activities.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, in the Mediterranean region, these practices have very often been accompanied by the construction of terraces, which are a very effective measure for soil conservation [10]. The massive presence of these structures, as long as they are well-maintained, decouples hillslopes and the fluvial system significantly [11], decreasing the hydrological response [12] and reducing the sediment transfer at the catchment scale [13]. However, the lack of maintenance after land abandonment leads to the deterioration and subsequent collapse of terraces, reactivating erosion and soil degradation processes [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies in the Mediterranean region (Ore and Bruins, 2012;Calsamiglia et al, 2017) have demonstrated the efficiency of agricultural terraces in promoting disconnectivity between the slopes and channels. However, abandonment of these terraces can generate concentrated runoff and sediment flows along preferential pathways created by the successive collapse of several terraces, promoting connections between these pathways and the main stream network (Calsamiglia et al, 2017). Changes in connectivity can explain changes in catchment runoff response and sediment yield (Meerkerk et al, 2009;López-Vicente et al, 2013a;Dung et al, 2015).…”
Section: Catchment Based Hydrology Under Post Farmland Abandonment Scmentioning
confidence: 99%